The barrio high schools of Tarlac their administration and supervision - Antonio, Paterno G. 1923- ([s.n.], 1971)
A contemporary body of knowledge on the administration of the barrio high schools along the following aspects: enrolment, organization, sources of funds and financing, qualifications of teachers and staffing, instructional facilities, instructional program and supervision of instruction, was organized. This study sought to describe the administration of the barrio high schools along the six mentioned aspects and compare the result with a contemporary picture.